(الحركة الموضعية في الخطاب القرآني وأثرها في الدلالة (دراسة بلاغية تحليلية - Abdelrahman Moawad Ali; Ragab Ibrahim Ahmed Awad; Elsayed Mohamed Salem Alawadi (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
لا شك أن رصد الخواص التركبية لصياغة الخطاب القرآني يساعد على الوصول إلى الدلالة، ولا أعني بالدلالة هنا الناتج الأول من الصياغة؛ لأن هذا الناتج يتحقق غالباً في أي مستوى تركيبي، جاءت الصياغة فيه على النمط المألوف، وإنما أعني الناتج الثاني، أو ما أطلق عليه عبد القاهر الجرجاني (المعاني الثواني) التي لا تبرز إلى حيز الإدراك العقلي إلا عندما تتلون الصياغة بإمكانات تعبيرية، وتحركات تركيبية، ومن المؤكد أن (المقام) يمثل أساس الدلالة، وافتقاده يؤدي إلى ورود مفردات متناثرة لا تحكمها علاقة ما؛ لأنها لم ترتبط بمقام يربط بين عناصرها، وعلى هذا فإن أية عملية تحليلية للصياغة لن تكون مُجدِية؛ لأنه من الضروري تصور المقام بهذا التحليل، ومع تصور هذا المقام تأخذ الصياغة أشكالاً متمايزة في حركتها التركيبية، حيث تمتد في اتجاهات مختلفة منها ما يذهب طولا، ومنها ما يذهب عرضا ومنها ما يأخذ عمقا موضعياً، وهو ما آثرت تسميته هنا  بالحركة الموضعية. ولا شك أن تتبع أثر تلك الحركات يعين على فهم دلالة الخطاب القرآني. من هنا جاءت هذه الدراسة الموسومة: "الحركة الموضعية في الخطاب القرآني وأثرها في الدلالة، دراسة بلاغية تحليلية". وقد قسمت هذا البحث بعد المقدمة إلى مبحثين تتلوهما خاتمة، وذلك على النحو التالي: المبحث الأول: وهو بعنوان "خصائص الخطاب القرآني" ويُستهل بإطلالة حول معنى الخطاب وأنواعه، ثم عرض لما تميز به أسلوب الخطاب في القرآن الكريم من سمات وخصائص عامة. المبحث الثاني: وهو بعنوان " الحركة الموضعية" وقد حاولت في هذا المبحث رصد العلاقة المبتدية بين الحركة الموضعية، والخطاب القرآني ومعزى هذه العلاقة. الخاتمة: وتضم أهم ما توصل إليه هذا البحث من نتائج . وقد أثبتُّ فى نهاية البحث قائمة بالمصادر والمراجع التى اعتمدت عليها في هذا البحث.There is no doubt that observing the compositional properties of the formulation of the Qur’anic discourse helps to reach the significance. I do not mean by significance here the first product of the formulation  Because this result is often achieved at any compositional level, the wording in it came in the familiar pattern, but I mean the second product, or what Abdel-Qaher Al-Jarjani called (the meanings of seconds) that does not emerge into the realm of mental perception except when the wording is colored with expressive capabilities, synthetic movements, and from  It is certain that (the maqam) represents the basis of significance, and lacking it leads to the emergence of dispersed vocabulary that is not governed by some relationship  Because it is not related to a denominator that links its elements, and therefore any analytical process of the formulation will not be feasible.  Because it is necessary to visualize the maqam with this analysis, and with the perception of this maqam, the formulation takes distinct forms in its compositional movement, as it extends in different directions, some of which go in length, some of which go in width, and some of them take a local depth, which is what I prefer to call here the local movement.  There is no doubt that tracking the impact of these movements helps to understand the significance of the Qur’anic discourse. Hence this study tagged: “The local movement in the Qur’anic discourse and its impact on significance, an analytical rhetorical study.”After the introduction, this research was divided into two topics that are followed by a conclusion, as follows: The first topic: It is titled “Characteristics of the Qur’anic Discourse” and begins with an overview of the meaning and types of discourse, and then presents the general characteristics and characteristics of the discourse style in the Holy Qur’an. The second topic: It is entitled "Local Movement". I tried in this section to monitor the primary relationship between positional movement, and the Qur'anic discourse and the significance of this relationship. Conclusion: It includes the most important results of this research. At the end of the research, a list of the sources and references that I relied on in this research was established.